INFLUENCE RATIO FINANCE TO PRICE SHARE IN MINING COMPANIES IN THE 2019-2022 PERIOD (Jurnal Ipteks Terapan, 2024)
Mining subsector companies also need to know the level of liquidity, solvency, activity and profitability to measure whether a company can perform well. All this has a significant impact on share prices, so if liquidity, solvency, activity or profitability are good or increasing in terms of profits, they indicate the company's ability to generate profits with its own capital and share prices. This is also influential because share prices can determine the success of a company whose market power is demonstrated to exchange through sell buy share company the in market capital.In study This time, researchers used quantitative research methods. Population used in This research consisted of 48 mining companies and a sample of 10 companies with a total of 40 observations. The data analysis technique used multiple linear regression analysis with SPSS version 26. The conclusion of this research is that partial profitability has a positive and significant effect on stock prices, partial liquidity. has no effect on share prices, Partial solvency has no effect on share prices, Partial activity has no effect on share prices, Partial market value has no effect on share prices and profitability, liquidity, solvency, activity and market value simultaneously have a positive and significant effect on share prices in mining companies in the 2019-2022 period.